The celebritization of self-care: The celebrity health narrative of Demi Lovato and the sickscape of mental illness. (February 2020) - Franssen, Gaston
Using the threatened yet ultimately reconfirmed celebrity status of pop singer and mental health advocate Demi Lovato as a case study, this article analyzes how celebrity health narratives reflect and produce a neoliberal ideology of individuality in the context of mental health care. It is argued that Lovato has successfully rebranded herself as the embodiment of achievement, self-improvement and confidence by embracing her diagnosis with bipolar disorder and other mental health struggles. Furthermore, the article demonstrates how her celebrity health narrative has been repackaged and reproduced by the merchandizing industry, providing general lifestyle advice about the value of ongoing self-improvement. This convergence between the 'sickscape' of mental illness and celebrity culture can be understood as a 'celebritization of self-care', which reproduces a hyper-individualized, neoliberal and distinctly gendered ideology of meritocracy, and presents all forms of achievement, including recovery from mental illness, as the result of competitive individualism.